2008
DOI: 10.1159/000121464
|View full text |Cite
|
Sign up to set email alerts
|

Colostrinin Decreases Hypersensitivity and Allergic Responses to Common Allergens

Abstract: Background: Colostrinin™ (CLN), isolated from mothers’ pre-milk fluid (colostrum), is a uniform mixture of low-molecular-weight, proline-rich polypeptides. CLN induces neurite outgrowth of pheochromocytoma cells, extends the lifespan of diploid fibroblast cells, inhibits β-amyloid-induced apoptosis and improves cognitive functions when administered to Alzheimer’s disease patients. Objective: The aim of this study was to investigate potential allergic responses to CLN and its impact on allergic sensitization an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
(68 reference statements)
6
15
0
Order By: Relevance
“…These data are in line with the findings that CLN significantly decreased levels of allergen-induced (ragweed pollen and house dust mite extract-specific) IgE/IgG1 levels, as well as mucin levels, and the recruitment of eosinophils in the airways of challenged, sensitized animals [38]. It has been also demonstrated that CLN has no ability to induce IgE antibodies, immediate cutaneous reactions, inflammation, mucin production or airway hyperresponsiveness [38]. Recent findings show that the epithelial gamma-aminobutyric acid (GABA)-ergic system has an essential role in asthma [39].…”
Section: Cln-mediated Changes In Gene Expression Related To Immune Fusupporting
confidence: 90%
See 3 more Smart Citations
“…These data are in line with the findings that CLN significantly decreased levels of allergen-induced (ragweed pollen and house dust mite extract-specific) IgE/IgG1 levels, as well as mucin levels, and the recruitment of eosinophils in the airways of challenged, sensitized animals [38]. It has been also demonstrated that CLN has no ability to induce IgE antibodies, immediate cutaneous reactions, inflammation, mucin production or airway hyperresponsiveness [38]. Recent findings show that the epithelial gamma-aminobutyric acid (GABA)-ergic system has an essential role in asthma [39].…”
Section: Cln-mediated Changes In Gene Expression Related To Immune Fusupporting
confidence: 90%
“…Our data suggest that CLN downregulates the expression of the gamma subunit of the Fc epsilon receptor as well as 24 ALDOC↓,ANXA3,ATP1A3↓,ATP1B1,ATP1B3,beta-estradiol,BTG2,CACNB1↓,CCDC80, CCNE2 (includes EG:9134),CDH11,ELK3↓, ERBB2,FLOT1,GPX3↓,HNRPH1↑,HRAS,HSD17B1↑, HTRA1,IGF2R,KRT19,ODF1↓,PBX1,PCDHGA3↓,PDIA4,RASA3↓,SC4MOL,SPAG4, SPINK4↓, TERT,THSD1↑,TMSB4X,TOP2A,TSC22D1,TSC22D4↓ 13 Cancer Reproductive system disease Tumor morphology 25 ADAMTS13↓,AMD1,ANGPT2,ANGPTL4↓,ANXA5,ATF1,CDC25B,CHRNB1,CLU,DST, ELAVL1,ETS2,F2,F8↓,GREM1,LAMP1,LENEP↓, LGMN↑,MSN,MYBL2,MYC,NFYB, POLR3D↑,PRPH↓,PRPH2↑,PRRG2↓,RFX1,ROM1,SLIT1↓,SNX2,SNX6↑,TADA2L↓,TGFBR2, TGFBRAP1↑,TOP2A 13 Cell death Digestive system development and function Tissue development JNK, protein kinase C (PKC), phospholipase A2 (cPLA2), and interleukin 13 (IL-13) expression. These data are in line with the findings that CLN significantly decreased levels of allergen-induced (ragweed pollen and house dust mite extract-specific) IgE/IgG1 levels, as well as mucin levels, and the recruitment of eosinophils in the airways of challenged, sensitized animals [38]. It has been also demonstrated that CLN has no ability to induce IgE antibodies, immediate cutaneous reactions, inflammation, mucin production or airway hyperresponsiveness [38].…”
Section: Cln-mediated Changes In Gene Expression Related To Immune Fusupporting
confidence: 84%
See 2 more Smart Citations
“…It affects cytokine induction [15,16] and amyloid β plaque formation, is believed to be an immunomodulator [16] and plays a role in the homeostasis of cellular redox and signal transduction. It also protects against spontaneous and induced mutations [17] , decreases allergic inflammation [18] , induces neurite outgrowth in cultured cells [19] , increases the lifespan of cultured cells by preventing mitochondrial dysfunction [20] and protects against amyloid-β -induced apoptosis in neuroblastoma cells [21] . A recent article investigating the mechanisms of the action of CLN, published in the Journal of Alzheimer's Disease [2] , reviewed the utility of CLN in the maintenance of physiological processes where oxidative stress has a causative role.…”
Section: Introduction To Colostrinin ™mentioning
confidence: 99%